2011
DOI: 10.3109/10428194.2011.578186
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in folate-related genes: impact on risk of adult acute lymphoblastic leukemia rather than pediatric in Han Chinese

Abstract: Folate metabolism plays an essential role in the processes of DNA synthesis and methylation. An aberrant folate metabolism caused by a genetic polymorphism may lead to genomic instability and affect the susceptibility to malignancies including acute lymphoblastic leukemia (ALL). This study was designed to explore the correlation between the polymorphisms in folate-related genes and the risk of ALL in Han Chinese. The DNA was isolated from 231 patients with pediatric ALL, 130 patients with adult ALL, and 367 he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 40 publications
2
20
3
Order By: Relevance
“…A range of factors might be related to the biologic mechanisms and etiology of ALL. It is generally considered that the development of ALL is a comprehensive result of environment, genetic risk factors, and gene-environment interactions (Robien et al, 2003;Scelo et al, 2009 (Yang et al, 2011). Poly-morphisms in genes involved in folate transport, metabolism, and distributionin vivo drew widespread attention in the last decade (McNeer 2011).…”
Section: Introductionmentioning
confidence: 99%
“…A range of factors might be related to the biologic mechanisms and etiology of ALL. It is generally considered that the development of ALL is a comprehensive result of environment, genetic risk factors, and gene-environment interactions (Robien et al, 2003;Scelo et al, 2009 (Yang et al, 2011). Poly-morphisms in genes involved in folate transport, metabolism, and distributionin vivo drew widespread attention in the last decade (McNeer 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have examined the role of DHFR variants in patients with ALL and reported conflicting results. A study by Yang et al [21] in Chinese population reported that DHFR317A>G mutant is not associated with the risk of ALL. In contrast to our study and Yang et al [21], Gomez-Gomez et al [19] reported -317 homozygous mutant genotypes (GG) to be a risk factor for the development of ALL in the Mexican population.…”
Section: Discussionmentioning
confidence: 99%
“…Functional polymorphisms in the DHFR gene can influence its expression or activity, thereby affecting the risk of folate-dependent diseases [19][20][21][22]. Polymorphisms in DHFR gene are also relevant in the context of sensitivity and resistance to antifolates [19,23,24] and antibacterial drugs, as they also affect the prognosis of such patients treated with these drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Further analysis stratified by cancer type showed 1420T allele was associated with a minor decreased risk only in leukemia, suggesting 1420T allele might be a protective factor for leukemia. It should be noted that the four relative small studies (Skibola et al, 2002;de Jonge et al, 2009;Lightfoot et al, 2010;Yang et al, 2011) with only 1572 cases and 1739 controls had driven the borderline inverse association, which may be due to selection bias. In stratifying analysis by source of control, the association between 1420T allele and reduced risk of cancer was significant in HB subgroup but not in PB subgroup.…”
Section: Discussionmentioning
confidence: 99%